Training To Make Aromatherapy Candles Using The Active Ingredients Of Coffee, Lemongrass And Lime In Tapak Gedung Village - Maryanti, Evi; Banon, Charles; Cahyani, Aswinda; Putri, Mutiara Wulandare ka Jolie; Hevio, M. Maqbul Farhansyah; Simanjuntak, Gresanty Oktavia; Kaus, Noor Haida Mohd (CV Media Inti Teknologi, 2024)
The purpose of this community service project is to transfer information and skills about the art of producing aromatherapy candles using natural ingredients like coffee, lemongrass, and lime to the residents of Tapak Gedung Village, Tebat Karai District, Kepahiang Regency. The technique used for community service projects in Tapak Gedung Village, Tebat Karai District, Kepahiang Regency, including teaching people how to make aromatherapy candles out of lime and coffee beans. The residents of Tapak Gedung Village, Tebat Karai District, Kepahiang Regency, have learned how to make aromatherapy candles from natural materials nearby, and this could lead to the residents of Tapak Gedung Village becoming financially independent. This is based on the outcomes of community service activities involving training in the production of aromatherapy candles from coffee beans and lime.